Analysis of influencing factors audit delay on registered banking firms on the Indonesian stock exchange before and during the pandemic period - Ikhsan, Arfan; Muda, Iskandar; Masatip, Anwari; Julvirta, Enos (Nurture, 2024)
Purpose: Audit delays reflect the timeliness of financial reporting. The lack of financial reports when required can render important information irrelevant. Shorter audit delays allow investors to make decisions more quickly which makes the information more valuable to them. This research aims to analyze the influence of auditor switching (AS), financial distress (FD), public accounting firm (PAF) reputation and the COVID-19 pandemic on AD. Design/Methodology/Approach: The population of research includes all firms in the financial sector listed on IDX for 2019-2022. This research uses purposive sampling where the samples are determined based on the researcher’s objectives. There were 176 companies selected as samples for each year of observation. Findings and Conclusion: The data are analyzed using descriptive statistics and multiple linear regression analysis. Based on the results of the test, AD is positively influenced by FD, AS has no effect on AD and AD is negatively impacted by PAF reputation. Furthermore, there is a significant difference in AD before and during the COVID-19 pandemic with audit delays being longer during the pandemic. Research Limitations/Implications: It is recommended to retest variables that have no effect on the study and include additional independent variables that may have an impact on audit completion performance to obtain a better understanding of why AD still exists in Indonesia for future research.